INVASIVE NON-TYPE B HAEMOPHILUS INFLUENZAE DISEASE: REPORT OF EIGHT CASES - Mariana Tresoldi das Neves Romaneli; Antonia Teresinha Tresoldi; Ricardo Mendes Pereira; Márcia Teixeira Garcia; Christian Cruz Hofling; Mariângela Ribeiro Resende (Sociedade de Pediatria de São Paulo, 2019)
ASTRACT Objective: To describe eight cases of invasive non-type b Haemophilus influenzae disease in children admitted to Hospital de Clínicas of Universidade Estadual de Campinas. Cases description: In 2015, there were eight cases of invasive non-type b H. influenzae disease. We tested the ampicillin sensitivity and beta-lactamase production of the strains identified and performed the genotyping. Molecular typing was determined by Pulsed-Field Gel Electrophoresis. Four patients were diagnosed with bacteremia; in two cases, H. influenzae was detected in the pleural fluid, and two patients had meningitis. Patients with comorbidities represented 37.5% of cases. Except for the strain of one patient - not sent to the reference laboratory -, all were ampicillin-sensitive and non-beta-lactamase-producing. Genotyping identified four non-capsular, one type c, and two type a strains. Molecular typing ruled out nosocomial transmission since all serotypes were distinct regarding genotype. Comments: The rise in cases of invasive non-type b H. influenzae infection was real. There was no nosocomial transmission, and we found no justification for the increase. These data indicate the need for surveillance to correctly diagnose, monitor, and understand the spectrum of non-type b H. influenzae disease.